Spatial heterogeneity of benthic biogeochemistry in two contrasted marine environments (Arcachon Bay and Bay of Biscay, SW France). (20th September 2016) - Mouret, Aurélia; Anschutz, Pierre; Deflandre, Bruno; Deborde, Jonathan; Canton, Mathieu; Poirier, Dominique; Grémare, Antoine; Howa, Hélène
Abstract: We have studied the heterogeneity of vertical profiles of biogeochemical components obtained from sediment core slicing. Sediment cores were collected in the intertidal zone of the Arcachon Bay and on the continental slope of the Bay of Biscay, at 550 and 1000 m depth. At each station of the Arcachon Bay, five 1 m-side zones were delimited at low tide. In each square, 3 cores were collected. Spatial heterogeneity on the continental slope was obtained from the study of 3 cores of multi-corer while 2 or 3 multi-corer deployments were used during the same oceanographic cruise. Similarity between profiles was determined to estimate the spatial heterogeneity at different scales. In the Arcachon Bay, results showed a spatial heterogeneity at a decimetre scale on apparently homogeneous areas. Despite the spatial variability, all the replicated profiles in Arcachon Bay sediments had similar trends, suggesting homogeneous benthic properties. However, a sampling with replicate cores handling is required for seasonal monitoring or study of biogeochemical mechanisms in coastal environments. We observe that the spatial variability on the continental margin of the Bay of Biscay is lower than in coastal environment of the Arcachon Bay. Heterogeneity is equivalent at a decimetre scale and at a hundred meters scale, which is the precision of the sampling positioning due to the drift of the boat and the tilt of the corer cable. In addition, our 10-year-long database for the Bay of Biscay showed that differences in the shape of profiles obtained in sediment cores collected at the same stations throughout this long period may not be interpreted in terms of evolution with time, because the observed variability is as high as the spatial heterogeneity.